Effects of chemically modified acorn starch on its functional characteristics and the sustained release properties of monolithic tablets - Saleh, Mohammed; Al-Ismail, Khalid; Mehyar, Ghadeer; Ajo, Radwan; Lee, Youngseung (Italian Journal of Food Science, 2025)
This study investigated the various chemical modifications that affect the functional properties of Acorn starch. Acorn starch was modified using octenyl succinic anhydride, sodium trimetaphosphate (STMP), oxidation, and lactic acid at different concentrations, with their impacts assessed at various temperatures. Octenyl succinic anhydride–treated samples exhibited swelling power ranging from 2.9% at 60°C to 10.4% at 90°C. Modification levels significantly decreased swelling power (P < 0.05), due to structural changes in amylose and amylopectin and stabilization of starch granules from cross-linking. Pasting viscosities increased with modification levels; for example, peak viscosity rose from 1736.0 to 2033.0 cP with octenyl succinic anhydride modification from 3.0 to 9.0%. Lactic acid modification resulted in the highest peak viscosities, whereas STMP cross-linkage showed the lowest. The highest water-holding capacity (WHC) of 139.8% was found with octenyl succinic anhydride at 45°C, while STMP at 0.5% had the lowest WHC. Syneresis varied from 6.80 to 25.30% across freeze–thaw cycles, being lowest with oxidation and highest with STMP. Chemical modifications generally reduced dissolution rates, with lactic acid-modified starch showing the lowest dissolution (58.7%) after 24 h. Results indicated that chemical modifications significantly impact the properties of Acorn starch, emphasizing the need for careful selection based on application.